Progress Told on Plans for CMA Building - Unknown (Unknown)
Preparation of plans for the new Administration Building at the California Maritime Academy are about 60 per cent complete, Capt. Henry E. Richter, USN (Ret.), academy superintendent, reported this week to the Academy, Board of Gorvernors.